Isolated congenital absence of the pericardium - Murat, Ayse; Artas, Hakan; Yilmaz, Erdal; Ogur, Erkin (Springer, 2008)
Absence of the pericardium can vary from partial to complete absence. Patients with complete absence of the pericardium are either asymptomatic or have nonspecific chest pain, and no treatment is needed. Patients with partial absence of the pericardium are at risk for possible symptomatic herniation of the left atrial appendage or left ventricle, leading to fatal myocardial strangulation. Therefore, it is very important to differentiate partial from complete absence of the pericardium. A 7-year-old girl presented with isolated congenital absence of the pericardium, which generally has a good prognosis. It is a relatively asymptomatic anomaly that usually requires no treatment. Some cases involve complications that require operative treatment. Absence of the pericardium can be precisely defined by computed tomography and magnetic resonance imaging.
Keywords: chest x-ray; magnetic resonance; pericardium